Iranian Students at the École des Beaux-Arts - Yahya Sepehri (صفه)
École des Beaux-Arts is considered as one of the most influential architecture schools in the world. During its relatively long life, this school admitted many students from different countries, including a number of Iranian architects and professors of architecture who were graduates of the École. The purpose of this study is to identify Iranian architecture students of the École des Beaux-Arts based on reliable documents. The main question of the research is how many Iranian students have studied at École des Beaux-Arts, and how was the quality of their education. Also, in what fields did these people work after graduation. This study tries to refer to the École’s documents to get the answers to the questions. The main sources of the research are primary. Examination of these documents shows that the number of Iranian students was 43, 29 of whom graduated. The presence of Iranians in the school is limited to the last four decades of the school’s life. The presence of Iranians in the 1960s is particularly significant. Iranian students left a relatively successful result in the École. They were able to win a number of medals and awards from the school. After graduating and returning to Iran, most of them held important positions in the field of education and architecture. Most of them became university professors and taught students in Iranian schools of architecture.